Health assessment of engineered structures : bridges, buildings, and other infrastructures - Haldar, Achintya (World Scientific, 2013)
This book covers some of the most recent developments and application potentials in structural health assessment for non-experts in the subject. Among topics addressed are sensor types, platforms and data conditioning for practical applications, wireless collection of sensor data, sensor power needs and on-site energy harvesting, long-term monitoring of structures, uncertainty in collected data, and future directions in structural health assessment.